2014
DOI: 10.1007/978-3-540-36045-2
|View full text |Cite|
|
Sign up to set email alerts
|

Vehicle Dynamics

Abstract: The use of general descriptive names, registered names, trademarks, service marks, etc. in this publication does not imply, even in the absence of a specific statement, that such names are exempt from the relevant protective laws and regulations and therefore free for general use. While the advice and information in this book are believed to be true and accurate at the date of publication, neither the authors nor the editors nor the publisher can accept any legal responsibility for any errors or omissions that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(27 citation statements)
references
References 0 publications
0
26
0
1
Order By: Relevance
“…The lateral acceleration needed as input to (12) is obtained by a linear single track model processing the steering angle input of the driver. Detailed presentations of the linear single track model are given in [1,36]. The single track model has been parametrized with the lateral acceleration and yaw rate measurements of two reference manoeuvres: firstly a constant radius cornering with increasing vehicle speed and secondly a manoeuvre consisting of several steering angle step inputs at a constant vehicle velocity.…”
Section: Double Lane Change Experimentsmentioning
confidence: 99%
“…The lateral acceleration needed as input to (12) is obtained by a linear single track model processing the steering angle input of the driver. Detailed presentations of the linear single track model are given in [1,36]. The single track model has been parametrized with the lateral acceleration and yaw rate measurements of two reference manoeuvres: firstly a constant radius cornering with increasing vehicle speed and secondly a manoeuvre consisting of several steering angle step inputs at a constant vehicle velocity.…”
Section: Double Lane Change Experimentsmentioning
confidence: 99%
“…Speed A depends on the acceleration of the vehicle under consideration (through a differential equation). According to [13], in this model only longitudinal motion can be simulated. Simulating the steering angle for overtaking maneuvers, for example, would require a more elaborate model, but this is out of the scope of our investigations.…”
Section: Physical Modelmentioning
confidence: 99%
“…A review of the existing software packages allowing fast and high precision kinematics and dynamics analysis of the road vehicles shows that most of them use MBS methodology. 2,3 The software packages have been usually used for vehicle dynamic simulation or vehicle control applications. It has been also shown that a computational MBS could be used for design optimization of vehicle dynamic subsystems.…”
Section: Introductionmentioning
confidence: 99%
“…The LPM models do not consider the suspension configuration and linkage geometry for simulation, analysis, and optimization of ride dynamics. A wide variety of LPMs has been developed 11 and they include quarter, 6,8 single-track half-car (bounce-pitch), 3,68 two-track half-car (bounce-roll), 11,12 and full-car 3,13 models. Comparatively, DPM considers the configuration and linkage geometry of the suspension.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation